2010
DOI: 10.1007/s12039-010-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Controlled release of 5-flurouracil from biomedical polyurethanes

Abstract: Novel biodegradable aliphatic poly(ether-urethane)s (PEUs) based on pluronic F-68 (PLF68) and castor oil were synthesized by the solution polymerization technique. These polymers were characterized by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic spectroscopy ( 1 HNMR) and gel permeation chromatography (GPC) to confirm the PEU formation and the molecular weight. Moderate molecular weight PEUs were obtained and converted into microspheres by solvent evaporation method to study the controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…It was clear from this study that the beads with more alginate survived in the PBS (pH 7.4) medium for the maximum time. Various polymeric systems, such as chitosan, gelatin, and hydroxyapatite, have been studied to investigate the release patterns of protein or drug from them . It was reported that a burst release of BSA was found in the case of a chitosan–alginate blend as a delivery system .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was clear from this study that the beads with more alginate survived in the PBS (pH 7.4) medium for the maximum time. Various polymeric systems, such as chitosan, gelatin, and hydroxyapatite, have been studied to investigate the release patterns of protein or drug from them . It was reported that a burst release of BSA was found in the case of a chitosan–alginate blend as a delivery system .…”
Section: Resultsmentioning
confidence: 99%
“…To fulfill that criterion, sodium alginate (SA) was blended with the synthesized PU, and partially crosslinked beads were prepared with a calcium chloride solution. The stability of the encapsulated protein during the processing, release, storage, safety, and biocompatibility of the degradable polymer is also very much necessary for controlled release applications . In the systemic delivery of proteins, biodegradable polymeric microspheres occupy an important place because of several aspects, such as the protection of sensitive proteins from degradation, the maintenance of the protein structure, sustained release patterns, and improved bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…The release behaviors of many other small molecular drugs were also studied, such as ibuprofen, 5-fl urouracil, etc. (Ring et al, 2008;Basa et al, 2009;Harisha et al, 2010). Beyond these small molecular drugs, Li et al (2009) incorporated rhBMP-2 (recombinant human bone morphogenetic protein) into polyurethane scaffolds implanted in rat femoral plug defects, and the research results clearly showed that at 4 weeks post-implantation, all rhBMP-2 treatment groups showed enhanced new bone formation relative to the scaffolds without rhBMP-2, an impressive improvement ( Figure 3.2 ).…”
Section: Polyurethane For Drugcontrolled Deliverymentioning
confidence: 99%
“…Therefore, CO can be used directly as a starting material for the preparation of polyurethanes, polyesters, polyamides, epoxy resins, and alkyd resins . Owing to their significant biocompatibility, vegetable oil‐based polyurethanes found interesting applications in biomedical area such as drug delivery systems, bone tissue engineering, bioadhesives, and wound dressing …”
Section: Introductionmentioning
confidence: 99%